2009
DOI: 10.1002/jrs.2298
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman spectroscopy of indanthrone and flavanthrone

Abstract: The normal Raman and surface-enhanced Raman scattering (SERS) spectra of flavanthrone and indanthrone were obtained at several excitation wavelengths. The spectral assignments were aided by density functional calculations. Since both molecules have very high symmetry (C 2h ) including a center of inversion, we expect that the modes of u symmetry will be forbidden in the normal Raman spectrum. However, proximity to the surface causes special SERS enhancement of several of the b u modes, along with somewhat weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…DFT calculations were performed with Gaussian 09 at the B3LYP level of theory and employing the 6‐31 + G* basis set. This basis set was chosen to be consistent with earlier works . No imaginary wavenumbers were observed in the calculated spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…DFT calculations were performed with Gaussian 09 at the B3LYP level of theory and employing the 6‐31 + G* basis set. This basis set was chosen to be consistent with earlier works . No imaginary wavenumbers were observed in the calculated spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Another indicator of current areas of importance in Raman spectroscopy is the XXII International Conference on Raman Table 1 Semiconductors and Nanoparticles (47), Time-Resolved Raman (8), and Tip-Enhanced Raman Spectroscopy (TERS) (21). These 497 posters give a general glimpse into the areas and their relative strength in the current practice of Raman spectroscopy.…”
Section: Icors 2010mentioning
confidence: 99%
“…The three structural isomers, all of which adsorb in the carboxylate form onto the silver nanoclusters, bind in two different geometries to the silver surface. Chang et al [47] measured the normal Raman and SERS spectra of flavanthrone and indanthrone at several excitation wavelengths, and the spectral assignments were aided by DFT calculations. As a final application of SERS, Agarwal and Reiner [48] used compacted powders of nano-and microparticles of silver to successfully induce SERS in spruce milled-wood lignin with near-infrared (NIR) laser excitation.…”
Section: Applications Of Sersmentioning
confidence: 99%
“…The molecule of interest, alizarin, is adsorbed onto an Ag nanoparticle substrate. The substrate is then irradiated with laser light (green), and the enhanced Raman scattering (red) is detected Geiman et al 2009;Chang et al 2009;Xie et al 2012;Bruni et al 2011a;Mayhew et al 2013;Benedetti et al 2014;Greeneltch et al 2012;Doherty et al 2014;Cañamares and Lombardi 2015;Zaffino et al 2015) can also be found in the literature. In addition to providing valuable reference spectra for identification purposes, these works have explored aspects such as the influence of pH on the resulting spectral patterns, and the binding geometry and relative orientation of the molecules examined with respect to the metal surface.…”
Section: Introductionmentioning
confidence: 99%